Sleep hygiene practice and sleep quality among undergraduate students in School of Health Sciences Universiti Sains Malaysia - Solihudin, Nurul Izzah (Universiti Sains Malaysia, 2023)
Undergraduate students are commonly vulnerable to suboptimal sleep quality due to increased academic demand. Sleep hygiene is a set of good sleep habits that is believed to be associated with sleep quality. A cross-sectional study was conducted to determine the level of practice of sleep hygiene, the level of sleep quality, and the association between sleep hygiene practice and sleep quality among undergraduate students in School of Health Sciences (SoHS), USM. The questionnaires used in this study were Sleep Hygiene Index (SHI) adopted from Mastin et al., (2006) and Pittsburgh Sleep Quality Index (PSQI) adopted from Buysse et al., (1989). A total of 201 undergraduate students who fulfilled the inclusion were involved in this study. They were selected by a simple random sampling method. Data collected were statistically analyzed by using the Statistical Package Social Science (SPSS) software version 26. This study shows that 116 (57%) respondents had poor sleep hygiene practice level. Meanwhile, 187 (93.0%) respondents have poor quality of sleep. This study also revealed that there is no significant association between sleep hygiene and quality of sleep among undergraduate students in School of Health Science, USM (p=0.243). This study’s finding demonstrated that most undergraduate students in School of Health Sciences USM have poor sleep hygiene and poor quality of sleep. Therefore, sleep education programs as an intervention and prevention strategy are suggested to improve sleep quality and adoption of sleep hygiene practice among students.